DAMPAK PANDEMI COVID 19 TERHADAP DUNIA PENDIDIKAN - Mungky Hendriyani; Ni Made Artini; Tatyana Tatyana (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2021)
Corona virus 2019 (COVID-19) is an infectious disease caused by acute corona virus 2 respiratory syndrome (SARS-CoV-2). So that the impact on the community and students can not meet directly on campus or in public places. Based on Nielsen's research entitled "Race Against the Virus, the Indonesian Consumer Response towards COVID-19" revealed that as much as 50% of Indonesian people began to reduce activities outside the home, and 30% of them said that they planned to shop more frequently online he temporary closure of all educational institutions as an effort to prevent the spread of an outbreak of Covid-19 worldwide has an impact on millions of students, including in Indonesia. Disturbances in the teaching and learning process directly between teacher and students as well as the termination of the assessment of learning have an impact on the psychological of students